STUDENT PERCEPTION ON BUSINESS ETHICS - Eko Suwardi; Arika Artiningsih; M. Ridwan Novmawan (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
Many research conducted on the behavior of business persons and their perception on business ethics. However, rarely similar study deals with the perception of students on business ethics. Indeed, students are our future generation who are going to have substantial role in Indonesian business and economy. Therefore this study focuses on students as a proxy for future business players in this country (Trawick and Draden, 1980). We compare among groups of students based on their maturity, formal business ethic education, gender and specific professional backgrounds. The results of analysis show that in general students have good perception on business ethics. Further, there is a significant different perception on business ethics among students with different academic maturity, professional background. Student with business background are less ethical compare to those are with non-business background. This may consistent with previous evidence found that ethical principles need to be introduced more to business students. In contrast, there is no different perception on business ethics among student with different gender groups and formal business ethics course. This could be business ethics formal education takes time to be internalized by participants or student with no formal business ethics course also learn business ethics from other sources.